Pterostilbene Activates the Nrf2-Dependent Antioxidant Response to Ameliorate Arsenic-Induced Intracellular Damage and Apoptosis in Human Keratinocytes - Zhou, Junfeng; Ci, Xinxin; Ma, Xiaoyuan; Yu, Qinlei; Cui, Yan; Zhen, Yu; Li, Shanshan (Frontiers in Pharmacology, 2019)
The NF-E2 p45-related factor 2 (Nrf2), a transcription factor that regulates the cellular adaptive response to oxidative stress, is a target for limiting tissue damage from exposure to environmental toxins, including arsenic. In the current study, we determine whether Pterostilbene (Pts), as a potent activator of Nrf2, has a protective effect on arsenic-induced cytotoxicity and apoptosis in human keratinocytes. Human keratinocytes (HaCaT) or mouse epidermal cells (JB6) were pretreated with Pts for 24 h prior to arsenic treatment. Harvested cells were analyzed by MTT, DCFH-DA, commercial kits, Flow cytometry assay and western blot analysis. Our results demonstrated that Pts effectively regulated the viability in HaCaT and JB6 cells, decreased the reactive oxygen species (ROS) generation and lipid peroxidation (MDA), and improved the NaAsO2-induced depletion of superoxide dismutase (SOD). Moreover, Pts treatment further dramatically inhibited NaAsO2-induced apoptosis, specifically the mitochondrial mediation of apoptosis, which coincided with the effective recovery of NaAsO2-induced mitochondrial membrane potential (ΔΨm) depolarization and cytochrome c release from the mitochondria. Furthermore, arsenic-induced decrease of anti-apoptotic factor Bcl-2 and Bcl-xl, and increase of pro-apoptotic factor Bax and Bad, as well as survival signal related factor caspase 3 acitvaiton were reversed by pts treatment. Further mechanistic studies confirmed that Pts increased antioxidant enzyme expression in a dose-dependent manner, which was related to Nrf2 nuclear translocation. In addition, the effects of Pts on NaAsO2-induced cell viability were largely weakened when Nrf2 was knocked down. Together, our results provide evidence for the use of Pts to activate the Nrf2 pathway to alleviate arsenic-induced dermal damage.